Effect of levothyroxine on major adverse cardiovascular events in patients with hypothyroidism and cardiovascular disease - Liu, Lijia; Zhang, Haiqing; Chen, Xiaowei; Liu, Zuoxiang; Zhao, Houyu; Ma, Shizhan; Zhao, Meng; Shen, Peng; Sun, Yexiang; Lin, Hongbo; Zhan, Siyan; Zhao, Jiajun; et al. (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to evaluate the effectiveness of levothyroxine, compared to non-levothyroxine treatment, in preventing adverse cardiovascular events and mortality in patients with hypothyroidism and cardiovascular disease (CVD).MethodsThis is a retrospective study utilizing medical record data from the Yinzhou Regional Health Care Database. The analysis included patients newly diagnosed with hypothyroidism between July 2006 and December 2021 who also had pre-existing CVD at the time when they received the first hypothyroidism diagnosis. The primary outcome measure was the occurrence of three-point major adverse cardiovascular events (3P-MACE), which included cardiovascular death, non-fatal myocardial infarction, and non-fatal stroke. Secondary outcomes comprised all-cause mortality, all-cause hospitalization, and cardiovascular-related hospitalization. Propensity score matching was used to match levothyroxine users with non-users on a 1:1 basis. Cox proportional hazard models were employed to compare the risk of outcomes between users and non-users, with hazard ratios (HRs) and 95% confidence intervals (CIs) reported.ResultsIn the matched cohort (n = 1,332 in each group), 417 patients experienced 3P-MACE. Compared to those not treated with levothyroxine, patients receiving levothyroxine showed a significantly reduced risk of 3P-MACE (HR, 0.67; 95% CI, 0.55–0.82, p < 0.01), all-cause death (HR, 0.24; 95% CI, 0.16–0.35, p < 0.01), all-cause hospitalization (HR, 0.23; 95% CI, 0.21–0.26, p < 0.01), and cardiovascular-related hospitalization (HR, 0.69; 95% CI, 0.59–0.82, p < 0.01).ConclusionsLevothyroxine may improve major cardiovascular outcomes and decrease all-cause hospital admissions in patients with hypothyroidism and CVD.